Cyberbullying against Rivals: Application of Key Theoretical Concepts Derived from Situational Action Theory. Issue 12 (2nd December 2021) - Shadmanfaat, Shamila; Richardson, Dustin A.; Muniz, Caitlyn N.; Cochran, John K.; Kabiri, Saeed; Howell, C. Jordan
ABSTRACT: We apply key theoretical concepts derived from, and test the predictive efficiency of, situational action theory on sports fans' decision to engage in cyberbullying perpetration against rivals. To do so, we employ self-report data from a random sample of 508 students from an Iranian university. Ordinary least squares regression is used to analyze these data. In accordance with situational action theory's propositions, both crime propensity and criminogenic exposure increase fans' decision to engage in cyberbullying perpetration. Additionally, the interaction of crime propensity and criminogenic exposure increases fans' engagement in cyberbullying perpetration, while the inclusion of the interaction term increases the model's predictive power. In contrast to Wikström's propositions, however, demographic variables (gender, age, education) remain significant even when situational action theory's constructs are added into the model.